Troponin I untuk memprediksi kejadian Kardiovaskular mayor Pasca bedah pintas arteri koroner - Siti Elkana Nauli; Ganesja M Harimurti; Nani Hersunarti (Jurnal Kardiologi Indonesia, 2010)
Background. CABG has impact in morbidity and mortality. Early detection for which patients will develop these outcomes should be done, especially in patients with low risk for morbidity and mortality after CABG. Elevated troponin I level is common after CABG but its prognostic value still confus-ing due to its lack of cut-off point. This phenomenon has an independent prognostic value for short and long term outcomes. The aim of this of this study was to find out the cut off value of troponin I which could predict MACE 30-day after elective isolated CABG. Methods. This is a retrospective cohort study included 284 patients after elective CABG. The CKMB level was measured on the 1st and 12nd hour after CABG, while the troponin I level was measured on 8th hours after CABG. We used the ROC curve for troponin I cut-off point. MACE in this research were heart failure or worsening heart failure, low cardiac output syndrome, and death in 30-day after elective isolated CABG.Results.There were 284 patients who were included in this research, 20,7% had MACE during 30 day after CABG. From bivariate analysis, his-tory of heart failure before CABG, ejection fraction less than 50% before operation, and troponin I level = 5 ng/ml was significantly predicts 30-days MACE after CABG. While from the multivariate analysis showed history of heart failure and troponin I level = 5 ng/ml was significantly increases MACE with OR 3 and 6,88. Troponin I was an independent predictor of MACE with sensitivity 70%.Conclusion.Troponin I was an independent predictor for 30-days MACE after elective isolated CABG with cut-off value 5 ng/ml.